(untitled) (Bangladesh Journal of Pharmacology, 2012)
The laxative effect of ethanolic seed extract of Croton penduliflorous was evaluated in loperamide-induced constipated male rats on daily basis for 7 days. The loperamide significantly (p<0.05) reduced the feed and water intake and the fecal parameters (number, water content and weight). The feed and water intake, number, water content and weight of fecal pellets were significantly reduced in both the constipated and 200 mg/kg body weight treated animals whereas these parameters increased in the 50 mg/kg body weight. The extract at 100 mg/kg body weight produced values that compared with the unconstipated and senokot-treated animals. The body weight was not significantly altered in the 50, 100 and senokot-treated group whereas it was increased significantly in the constipated animals. The GIT ratio decreased in both the loperamide and 200 mg/kg body weight of the extract whereas the ratio at the 50 and 100 mg/kg body weight of the extract compared well with control animals. Overall, the ethanolic seed extract of C. penduliflorous produced a profound laxative activity against loperamide-induced constipated rats.